A simple dislocation model of deformation resistance of ultrafine-grained materials explaining Hall-Petch strengthening and enhanced strain rate sensitivity - Blum, Wolfgang; Zeng, Xiaohui (Acta Materialia, 2009)
WW1::794

A simple dislocation model of the influence of high-angle boundaries on the deformation behavior of ultrafine-grained materials - Blum, Wolfgang; Eisenlohr, Philip (Journal of Physics : Conference Series, 2010)
WW1::832

Coarsening of precipitates and degradation of creep resistance in tempered martensite steels - Chilukuru, Hemambar; Durst, Karsten; Wadekar, S.; Schwienheer, M.; Scholz, A.; Berger, C.; Mayer, K. H.; Blum, Wolfgang (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2009)
WW1::796
Keywords: kernfusionsrelevant

Control of dynamic recovery and strength by subgrain boundaries - Insights from stress-change tests on CaF2 single crystals - Mekala, Subba Rao; Eisenlohr, Philip; Blum, Wolfgang (Philosophical Magazine, 2011)
WW1::865

Correct Interpretation of Creep Rates: A Case Study of Cu - Blum, Wolfgang; Dvorak, J.; Kral, P.; Eisenlohr, Philip; Sklenicka, V. (Journal of Materials Science & Technology, 2015)
WW1::1050
Keywords: Creep and Fatigue

Corrigendum to “A simple dislocation model of deformation resistance of ultrafine-grained materials explaining Hall-Petch strengthening and enhanced strain rate sensitivity” (Acta Materialia (2009) 57 (1966-1974)) - Blum, Wolfgang; Zeng, X. H. (Acta Materialia, 2011)
WW1::912
Keywords: Creep and Fatigue; Simulation and Modeling; Nanomaterials

Creep behavior of an AlTiVNbZr0.25 high entropy alloy at 1073 K - Kral, Petr; Blum, Wolfgang; Dvorak, Jiri; Yurchenko, Nikita; Stepanov, Nikita; Zherebtsov, Sergey; Kuncicka, Lenka; Kvapilova, Marie; Sklenicka, Vaclav (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2020)
The deformation behavior of an AlTiVNbZr0.25 high entropy alloy at 1073 K was investigated in creep in protective argon atmosphere at stresses of 100–560 MPa with and without changes. In the initial condition after annealing at 1473 K for 24 h the alloys was composed of B2 matrix phase and coarse Zr5Al3-type particles. During creep a limited amount of new Nb2Al-type sigma phase precipitates at the Zr5Al3/B2 hetero-phase interface and a quasi-stationary dislocation density of the expected order of magnitude are developed. The quasi-stationary creep rate obeys a three-power law and the transients after stress changes are inverted. This is interpreted in terms of the class A creep behavior with viscous glide due to cloud drag.
CRIS-Team Scopus Importer:2020-04-14
Keywords: Creep; Deformation mechanisms; High Entropy alloys; Microstructure; Phase transformations; Viscous glide

Creep Behavior of Bulk Nanostructured Materials - Time-Dependent Deformation and Deformation Kinetics - Blum, Wolfgang; Eisenlohr, Philip; Sklenička, Vaclav (Bulk Nanostructured Materials, 2009)
Created from Fastlane, Scopus look-up
Keywords: Bulk nanostructured materials; Creep behavior; Deformation kinetics; Deformation resistance; Time-dependent deformation

Creep transients during stress changes in ultrafine-grained copper - Kapoor, R.; Li, Yujiao; Wang, J. T.; Blum, Wolfgang (Scripta Materialia, 2006)
Stress change tests were conducted on ultrafine-grained Cu in a region where the grain size is smaller than the steady state subgrain size. After stress reduction the normal creep transients were absent, confirming subgrain strengthening in conventional grain-sized materials and a lack of steady state subgrain structure in the ultrafine-grained materials. © 2006 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Equal channel angular pressing (ECAP); Severe plastic deformation; Subgrain boundary; Transients; Ultrafine-grained Cu

Deformation kinetics of coarse-grained and ultrafine-grained commercially pure Ti - Blum, Wolfgang; Li, Yujiao; Breutinger, Falk (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2007)
The elevated temperature deformation kinetics of ultrafine-grained (UFG) Ti of commercial purity (grade 2) produced by equal channel angular pressing (ECAP) at elevated temperature was measured and compared to that of coarse-grained (CG) Ti. Like CG Ti, the UFG Ti exhibits dynamic strain aging effects related to transition between jerky glide of dislocations without solute cloud and viscous glide with cloud. In the jerky region the yield stress of UFG Ti is distinctly enhanced compared to CG Ti. The steady state deformation resistances of CG and UFG Ti are not significantly different. The jerky → viscous transition results in a relative maximum of deformation resistance as function of strain, which is explained by the opposing effects of cloud formation and coarsening of dislocation structure. The high content of grain boundaries and dislocations in the initial state of UFG Ti stabilizes the material against break-away of dislocations from their clouds. © 2006 Elsevier B.V. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Deformation kinetics; Dislocation model; Dynamic strain aging; Solute clouds; Transition; UFG Ti

Deformation kinetics of nanocrystalline nickel - Li, Yujiao; Müller, Johannes; Höppel, Heinz Werner; Göken, Mathias; Blum, Wolfgang (Acta Materialia, 2007)
The work hardening and the strain rate sensitivity of flow stress were studied in the temperature range from 298 to 473 K for nanocrystalline (NC) nickel with average grain sizes of about 25 and 80 nm produced by pulsed electrodeposition. The rate of work hardening, the maximum flow stress and the strain rate sensitivity of flow stress increase with decreasing grain size. The data are compared to published data for NC Ni and found to be consistent. The common analysis of strain rate sensitivity in terms of thermal activation is critically discussed. It is proposed that the activation analysis gives information about thermally activated processes at grain boundaries which may be related with recovery of dislocations.
Created from Fastlane, Scopus look-up
Keywords: Activation volume; Grain boundaries; Nanocrystalline Ni; Strain rate sensitivity; Work hardening

Deformation resistance in the transition from coarse-grained to ultrafine-grained Cu by severe plastic deformation up to 24 passes of ECAP - Blum, Wolfgang; Li, Y. J.; Zhang, Y.; Wang, J. T. (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2011)
WW1::868

Development of new 11%Cr heat resistant ferritic steels with enhanced creep resistance for steam power plants with operating steam temperatures up to 650 °C - Wang, Y.; Mayer, K. -H.; Scholz, A.; Berger, C.; Chilukuru, Hemambar; Durst, Karsten; Blum, Wolfgang (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2009)
WW1::801
Keywords: kernfusionsrelevant

Discussion: Activation volumes of plastic deformation of crystals - Blum, Wolfgang (Scripta Materialia, 2018)
Two data sets reporting apparent activation volumes V-app of plastic deformation of ultrafine-grained Cu are compared. They differ strongly in magnitude and stress dependence of Vapp. It is suggested that the difference results from differences in testing method. While Vapp from stress relaxations appears to be consistent with expectations for the activation of thermally activated glide of dislocations in the bulk of the material, Vapp from rate change tests appears to characterize the quasi-stationary deformation where dynamic recovery plays a major role. This underscores the necessity to specify which of the various thermally activated subprocesses of deformation are tested. (C) 2017 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.

Dislocation glide velocity in creep of Mg alloys derived from dip tests - Eisenlohr, Philip; Blum, Wolfgang; Milicka, K. (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2009)
WW1::802

Dislocation mechanics of creep - Blum, Wolfgang; Eisenlohr, Philip (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2009)
WW1::803

Dynamic recovery in nanocrystalline Ni - Sun, Z.; Van Petegem, Steven; Cervellino, A.; Durst, Karsten; Blum, Wolfgang; Van Swygenhoven, H. (Acta Materialia, 2015)
WW1::1022

Effect of grain refinement by ECAP on creep of pure Cu - Blum, Wolfgang; Dvorak, J.; Kral, Petr; Eisenlohr, Philip; Sklenicka, V. (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2014)
WW1::994

Erratum: A simple dislocation model of deformation resistance of ultrafine-grained materials explaining Hall-Petch strengthening and enhanced strain rate sensitivity (Acta Materialia (2009) 57 (1966-1974)) - Blum, Wolfgang; Zeng, X. H. (Acta Materialia, 2011)
WW1::872

Evolution of dislocation structure and deformation resistance in creep exemplified on single crystals of CaF2 - Sadrabadi, Peiman; Eisenlohr, Philip; Wehrhan, G.; Staeblein, J.; Parthier, L.; Blum, Wolfgang (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2009)
WW1::804

Evolution of microstructure and deformation resistance in creep of tempered martensitic 9-12%Cr-2%W-5%Co steels - Agamennone, Roberto; Blum, Wolfgang; Gupta, Chiradeep; Chakravartty, Jayanta K. (Acta Materialia, 2006)
The microstructural evolution during creep at 923 K of four tempered martensite 9-12%Cr-steels modified with 2%W and 5%Co was quantified by electron microscopy. Coarsening of subgrains with strain towards the stress dependent steady state was confirmed. The evolution of the precipitate structure is similar with regard to M23C6 (M: metallic element, X: N, C) and Laves phase (Fe,Cr)2(W,Mo) but differs strongly with regard to V-bearing precipitates. Low temper temperatures promote precipitation of V as M2X instead of VX. This appears to be critical in causing anomalously fast breakdown of initially high creep resistance. Dissolution of small V-bearing precipitates and corresponding loss of precipitation hardening in the subgrain interior is proposed to be the reason for this breakdown. The dissolution is caused by fast coarsening of M2X precipitates and precipitation of Z-phase at subgrain boundaries. Large M2X precipitates at subgrain boundaries are proposed to be nucleation sites of Z-phase. © 2006 Acta Materialia Inc.
Created from Fastlane, Scopus look-up
Keywords: Creep; Precipitates; Subgrains; Tempered martensite steels; Z-phase

Flow stress and creep rate of nanocrystalline Ni - Blum, Wolfgang; Li, Yujiao (Scripta Materialia, 2007)
Stress-strain curves of nanocrystalline Ni are compared to reported creep rate-strain curves at 298 and 373 K. Both show a limited range of strong work hardening followed by a steady-state. The stress dependence of the steady-state creep rate explains the continuous decrease in creep rate found in tests at constant load. The stress exponent of strain rate, n, decreases markedly with decreasing stress, but does not reach the low level commonly expected for Coble creep or grain boundary sliding.
Created from Fastlane, Scopus look-up
Keywords: Creep rate; Flow stress; Nanocrystalline Ni; Steady-state; Stress exponent

Harper-Dorn creep - Kassner, Michael E.; Kumar, Praveen; Blum, Wolfgang (International Journal of Plasticity, 2007)
The fundamental mechanism of time-dependent plasticity, or creep, of crystalline materials at very low stress is, at present, particularly controversial. At "moderate" stresses above about 0.6 Tm, over a wide range of stresses, five-power-law creep is observed that is widely believed to be dislocation climb-controlled, with the activation energy for creep to be close to that of vacancy diffusion. Steady-state creep (Stage II or secondary creep) is usually described by the steady-state stress exponent, n, which is typically 4-7. At lower stresses, Harper-Dorn has usually been the mechanism suggested to occur. The relation between the applied stress and the steady-state creep-rate for Harper-Dorn creep is phenomenologically described byover(ε, ̇)ss = AHD fenced(frac(Dsd Gb, kT)) fenced(frac(σ, G))1where AHD is a constant. Since these early observations, Harper-Dorn creep has been reported to occur in many materials. Recent observations have suggested that in Al (the most extensively studied system) and all other systems, Harper-Dorn may be artificial in that the high creep rates may be a consequence of additional or unusual restoration mechanisms that do not normally occur in five-power-law creep or tensile fracture. These restoration mechanisms include dynamic recrystallization and/or grain growth. Others have suggested that Harper-Dorn is also artificial but because the strain-rates reported were not genuinely steady-state and, consequently, as much as an order of magnitude higher than genuine steady-state behavior. Others also found that they could not reproduce the original Al data of Harper and Dorn, for unknown reasons. The analysis of other materials in which Harper-Dorn has been proposed to occur has been placed in question. © 2006 Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Ceramics; Creep; Harper-Dorn

Influence of grain boundaries on the deformation resistance: Insights from an investigation of deformation kinetics and microstructure of copper after predeformation by ECAP - Bach, Jochen; Liebig, Jan Philipp; Höppel, Heinz Werner; Blum, Wolfgang (Philosophical Magazine, 2013)
WW1::968

In situ study of microstructure and strength of severely predeformed pure Cu in deformation at 573K - Blum, Wolfgang; Dvorak, J.; Kral, P.; Petrenec, M.; Eisenlohr, Philip; Sklenicka, V. (Philosophical Magazine, 2015)
WW1::1052
Keywords: Nanomaterials

Interpretation of unloading tests on nanocrystalline Cu in terms of two mechanisms of deformation - Blum, Wolfgang; Eisenlohr, Philip; Hu, Jiangjiang (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2016)
WW1::1064

Mechanisms of creep deformation in steel - Blum, Wolfgang (Creep-Resistant Steels, 2008)
Created from Fastlane, Scopus look-up

Modelling the transition from strengthening to softening due to grain boundaries - Zeng, Xiaohui; Eisenlohr, Philip; Blum, Wolfgang (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2008)
WW1::777

New method of determining stress relaxation behavior in creep machines by controlled unloading - Blum, Wolfgang; Breutinger, Falk (International Journal of Materials Research, 2002)
Conventional measurement of stress relaxation in tests with constant total (elastic plus inelastic plus thermal) strain requires high resolution and excellent control of strain and is perturbed by thermal fluctuations. A new method for measuring the stress relaxation behavior is presented which avoids these experimental problems. It is based on the fact that the stress relaxation behavior is fully contained in the relation between inelastic strain rate and stress at given mechanical strain. Consequently, it should be possible to measure stress relaxation in creep machines when stepwise unloading is performed such that the inelastic strain rate can be determined at constant mechanical strain. This is confirmed by tests on the Mg-base alloy AZ91.
CRIS-Team WoS Importer:2022-01-14

New observations on high-temperature creep at very low stresses - Kumar, Praveen; Kassner, Michael E.; Blum, Wolfgang; Eisenlohr, Philip; Langdon, Terence G. (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2009)
WW1::820

On the elevated-temperature deformation behavior of polycrystalline Cu subjected to predeformation by multiple compression - Li, Yujiao; Zeng, Xiaohui; Blum, Wolfgang (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2008)
WW1::780

On the Hall-Fetch relation between flow stress and grain size - Blum, Wolfgang; Li, Yujiao; Chen, J.; Zeng, Xiaohui; Lu, K. (International Journal of Materials Research, 2006)
Data of flow stresses a for pure Cu with ultrafine grains with grain size d ≈ 0.35 μm produced by severe plastic deformation and grains of conventional size obtained in the range of homologous temperatures T hom from 0.22 (room temperature) to 0.33 are compared to data for hardnesses H for Cu of various grain structures from single crystalline to d = 0.01 μm measured by nanoindentation at room temperature. The two sets of data appear to be consistent when σ ≈ H/3. At room temperature the Hall-Fetch relation holds, i.e., the flow stress increases monotonically with decreasing grain size by Δ σ ∝ d-0.5. At elevated Thom the saturated flow stress decreases when the grains become ultrafine. The transition from hardening to softening by grain boundaries in the saturation stage is discussed on the basis of a simple statistical dislocation model considering the influence of grain boundaries on the balance between generation and annihilation of dislocations.
Created from Fastlane, Scopus look-up
Keywords: Flow stress; Hall-Fetch; Ultra fine grains

On the validity of the natural creep law at low stresses - Blum, Wolfgang (Materialia, 2021)
Singh et al. interpreted their recent results on creep of LiF single crystals at extremely low stresses and creep rate as violation of the ‘natural’ steady state creep law. Re-analysis of their data indicates that this interpretation is not conclusive due to the uncertainty in definition of the steady state caused by the strain dependence of creep rate and the systematic reduction of the stress exponent of the creep rate with decreasing stress as the mean free path of dislocations approaches the specimen size (‘size effect’).
CRIS-Team Scopus Importer:2021-04-02

Quantification of dislocation structures at high resolution by atomic force microscopy of dislocation etch pits - Sadrabadi, Peiman; Durst, Karsten; Göken, Mathias; Blum, Wolfgang (Philosophical Magazine Letters, 2009)
WW1::823

Quantifying the distributions of dislocation spacings and cell sizes - Eisenlohr, Philip; Sadrabadi, Peiman; Blum, Wolfgang (Journal of Materials Science, 2008)
WW1::782

Quasi-Stationary Strength of ECAP-Processed Cu-Zr at 0.5 T-m - Blum, Wolfgang; Dvorak, Jiri; Kral, Petr; Eisenlohr, Philip; Sklenicka, Vaclav (Metals, 2019)
The influence of the grain structure on the tensile deformation strength is studied for precipitation-strengthened Cu-0.2%Zr at 673K. Subgrains and grains are formed by equal channel angular pressing (ECAP) and annealing. The fraction of high-angle boundaries increases with prestrain. Subgrains and grains coarsen during deformation. This leads to softening in the quasi-stationary state. The initial quasi-stationary state of severely predeformed, ultrafine-grained material exhibits relatively high rate-sensitivity at relatively high stresses. This is interpreted as a result of the stress dependences of the quasi-stationary subgrain size and the volume fraction of subgrain-free grains.
CRIS-Team WoS Importer:2020-01-10

Role of boundaries in control of deformation rate and strength of crystalline materials - Blum, Wolfgang (Materials Science Forum, 2009)
Plastic deformation of crystalline materials is not controlled by interaction among free dislocations only, but the interaction of free dislocations with internal boundaries. i) Low-angle boundaries: Modeling of deformation of pure materials with conventional grain size on the basis of structure evolution indicates that low-angle boundaries act as obstacles of free dislocations. The migration of the low-angle boundaries constitutes an essential recovery process determining the deformation resistance in the steady state. ii) High-angle boundaries: Severe plastic deformation transforms low-angle boundaries into high-angle ones. They differ in obstacle and recovery characteristics from low-angle boundaries, which explains the special properties of ultrafine-grained and nanocrystalline materials with regard to strength, strain rate sensitivity and ductility. iii) Phase boundaries in Ni-base superalloys enhance the strengthening by hard phases with strengthening by dense dislocation networks serving to reduce coherency stresses. It is concluded that internal boundaries play a crucial role in controlling the evolution of structure and strength in crystalline materials. © (2009) Trans Tech Publications.
Created from Fastlane, Scopus look-up
Keywords: Annihilation of dislocations; Creep rate; Deformation resistance; Dislocation structure; Flow stress; Generation of dislocations; High-angle boundaries; Low-angle boundaries; Nanostructured materials; Phase boundaries; Steady state deformation

Role of boundaries in control of deformation rate and strength of crystalline materials - Blum, Wolfgang (Materials Science Forum, 2009)
WW1::825

Stability of ultrafine-grained Cu to subgrain coarsening and recrystallization in annealing and deformation at elevated temperatures - Blum, Wolfgang; Li, Yujiao; Durst, Karsten (Acta Materialia, 2009)
WW1::827

Strain Rate Contribution due to Dynamic Recovery of Ultrafine-Grained Cu-Zr as Evidenced by Load Reductions during Quasi-Stationary Deformation at 0.5 T-m - Blum, Wolfgang; Dvorak, Jiri; Kral, Petr; Eisenlohr, Philip; Sklencka, Vaclav (Metals, 2019)
During quasi-stationary tensile deformation of ultrafine-grained Cu-0.2 mass%Zr at 673 K and a deformation rate of about 10(-4) s(-1) load changes were performed. Reductions of relative load by more than about 25% initiate anelastic back flow. Subsequently, the creep rate turns positive again and goes through a relative maximum. This is interpreted by a strain rate component E- associated with dynamic recovery of dislocations. Back extrapolation indicates that E- contributes the same fraction of (20 +/- 10)% to the quasi-stationary strain rate that has been reported for coarse-grained materials with high fraction of low-angle boundaries; this suggests that dynamic recovery of dislocations is generally mediated by boundaries. The influence of anelastic back flow on E- is discussed. Comparison of E- to the quasi-stationary rate points to enhancement of dynamic recovery by internal stresses. Subtraction of
CRIS-Team WoS Importer:2020-01-10

Structural stability of ultrafine-grained copper - Li, Yujiao; Blum, Wolfgang; et al. (Scripta Materialia, 2008)
WW1::785

Structure evolution and deformation resistance in production and application of ultrafine-grained materials - The concept of steady-state grains - Blum, Wolfgang; Eisenlohr, Philip (Materials Science Forum, 2011)
WW1::902

Temperature dependence of the strength of fine- and ultrafine-grained materials - Schneibel, J. H.; et al. (Acta Materialia, 2011)
WW1::906

The effect of predeformation on creep strength of 9% cr steel - Král, Petr; Dvořák, Jiří; Blum, Wolfgang; Sklenička, Václav; Horita, Zenji; Takizawa, Yoichi; Tang, Yongpeng; Kunčická, Lenka; Kocich, Radim; Kvapilová, Marie; Svobodová, Marie (Materials, 2020)
Martensitic creep-resistant P92 steel was deformed by different methods of severe plastic deformation such as rotation swaging, high-pressure sliding, and high-pressure torsion at room temperature. These methods imposed significantly different equivalent plastic strains of about 1–30. It was found that rotation swaging led to formation of heterogeneous microstructures with elongated grains where low-angle grain boundaries predominated. Other methods led to formation of ultrafine-grained (UFG) microstructures with high frequency of high-angle grain boundaries. Constant load tensile creep tests at 873 K and initial stresses in the range of 50 to 300 MPa revealed that the specimens processed by rotation swaging exhibited one order of magnitude lower minimum creep rate compared to standard P92 steel. By contrast, UFG P92 steel is significantly softer than standard P92 steel, but differences in their strengths decrease with increasing stress. Microstructural results suggest that creep behavior of P92 steel processed by severe plastic deformation is influenced by the frequency of high-angle grain boundaries and grain coarsening during creep.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Creep-resistant 9% Cr steels; Microstructure; Severe plastic deformation

The influence of long-term annealing at room temperature on creep behaviour of ECAP-processed copper - Blum, Wolfgang; et al. (Materials Letters, 2017)
Present work investigates the effect of long-term annealing at low homologous temperature (similar to 0.22 T-m) on creep behaviour of pure copper (99.99%) processed by equal-channel angular pressing (ECAP). Coarse-grained pure copper was processed by 1 and 8 ECAP passes at room temperature. The ECAP-processed specimens were annealed at room temperature for 3 years. Microstructures of ECAP-processed specimens and their room temperature-annealed states were investigated by electron back scatter diffraction (EBSD) technique. Tensile tests were performed at room temperature under constant rate and at 373 Kin creep under constant load. It was found that long-term annealing at room temperature led to occurrence of large grains in microstructure which influenced the strength. The influence grew with number of ECAP passes.
Keywords: Equal-channel angular pressing (ECAP); Ultrafine-grained microstructure; Creep behaviour; Microstructure stability

Thermally activated flow in soft and hard regions: Getting information on work hardening strain and recovery strain from rate change tests - Blum, Wolfgang; Eisenlohr, Philip; Prell, M.; Durst, Karsten (Kovove Materialy-Metallic Materials, 2015)

Thermally activated flow in soft and hard regions: Getting information on work hardening strain and recovery strain from rate change tests - Blum, Wolfgang; Eisenlohr, P.; Prell, M.; Durst, K. (Kovove Materialy-Metallic Materials, 2015)
WW1::1037

Transmission electron microscopy study of strain-induced low- and high-angle boundary development in equal-channel angular-pressed commercially pure aluminum - Cabibbo, M.; Blum, Wolfgang; Evangelista, E.; Kassner, M. E.; Meyers, M. A. (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2008)
The evolution of the microstructure in a commercially pure aluminum during equal channel angular pressing (ECAP) using route BC was investigated by transmission electron microscopy. Subgrains, or cells, form, which have both high (φ > 15 deg) and low (φ < 15 deg) misorientation. Misorientations and spacings of cell boundaries were determined from about 250 boundaries per pass of ECAP cell boundaries on the basis of Kikuchi patterns and Moiré fringes. The average cell size and misorientation saturate within the first two passes. Misorientations and spacings of high-angle boundaries decrease with the number of passes. After eight passes, the cell size is ≈1.3 μm and the fraction of high-angle boundaries is ≈0.7. The marked differences in the rate of grain structure evolution per pass are linked to differences in the ability of dislocations introduced in new passes to recombine with the existing ones. With increasing ECAP strain, the distribution of misorientations develops strong deviations from the MacKenzie distribution for statistical grain orientation. This is interpreted as a result of the tendency to form equiaxed grains in a textured grain structure. © The Minerals, Metals & Materials Society and ASM International 2007.
Created from Fastlane, Scopus look-up

What is "stationary" deformation of pure Cu? - Blum, Wolfgang; Dvorak, J.; Kral, Petr; Eisenlohr, Philip; Sklenicka, V. (Journal of Materials Science, 2014)
WW1::1016